CONCURRENT REGIONAL ELECTIONS PHENOMENON AS A POLITICAL RECRUITMENT IN INDONESIA - Dedi Mulyadi (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Concurrent regional election is a phenomenon in local democracy development in Indonesia. Many Efforts are performed to political recruitment. Yet, the implementation among expectations, aspirations and reality are frequently impaired proven by many problems in the implementation of the local democracy itself. The research applied normative juridical approach by identifying the problem in for complete background of the implementation of concurrent regional elections in Indonesia, its problems and solution. This research is expected to generate specific alternative insight through formulation of policy. It is expected to be a solution of any concurrent regional elections problems, a permanent rather than ad-hoc concept for the regional election, and a formulation of general regulation (lex generalis) on election which summarizes the present election regulation (lex specialist). These changes are internalized in continuing learning concept that can create academics, practitioners and technocrats on election. Keywords: democracy, local democracy, political positions, regional election and political recruitment.